THE EFFECT OF HEALTH EDUCATION WITH AUDIOVISUAL MEDIA ON THE LEVEL OF KNOWLEDGE AND SKILLS OF EARLY DETECTION OF FIBROADENOMA MAMMAE (FAM) IN YOUNG WOMEN AT SMA IBRAHIMY WONGSOREJO - Suci Anggraeni; Sarifatul Anisaro; Nur Yeni Hidajaturrokhmah; Nining Istighosah; Reni Yuli Astutik; Aprilia Nurtika Sari (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2023)
The lack of knowledge and skills of young women about breast self-examination to detect fibroadenoma mammae is caused by the lack of information among young women about early detection of fibroadenoma mammae. The purpose of this study was to determine the effect of health education with audiovisual media on the level of knowledge and skills of early detection of fibroadenoma mammae (FAM) in adolescent girls at SMA Ibrahimy Wongsorejo. This study uses a quasi-experimental quantitative research design with the Non Equivalent Control Group Design method, with a Stratified Random Sampling technique obtained a sample of 125 students. The dependent variable is health education with audiovisual, the independent variable is the level of knowledge and skills of young women. Data analysis used Wilcoxon test and Mc Nemar test. The results showed that in the intervention group there were 55 respondents (87.3%), while in the control group there were 3 respondents (4.8%). And it was found that young women who had qualified skills in the intervention group were 63 respondents (100%) while in the control group 31 respondents (49.2%). The results of the Wilcoxon and Mc Nemar Test statistical tests obtained a significance value of 0.000 (<0.05), it can be concluded that there is an effect of health education with audiovisual media on the level of knowledge and skills of early detection of fibroadenoma mammae (FAM) in adolescent girls at SMA Ibrahimy Wongsorejo. Audiovisual media is effective for increasing knowledge and skills of early detection of fibroadenoma mammae in young women because respondents can not only listen to the material given, but also see firsthand the steps for early detection of fibroadenoma mammae on video.